Treatment of patients with metastatic epidural spinal cord compression using an enhanced recovery after surgery program - Lei, Mingxing; Zheng, Wenjing; Cao, Yuncen; Cao, Xuyong; Shi, Xiaolin; Su, Xiuyun; Liu, Yaosheng (Frontiers in Cell and Developmental Biology, 2023)
Purpose: The aims of this study were to introduce a new medical, pathway based on the concept of ‘enhanced recovery after surgery’ (ERAS) for patients with metastatic epidural spinal cord compression (MESCC), and to test whether the ERAS program could improve clinical metrics among such patients. Methods: Data from patients with MESCC (n = 98), collected between December 2016 and December 2019 (Non-ERAS cohort), and from 86 patients with MESCC collected between January 2020 and December 2022 (ERAS cohort), were retrospectively analyzed. Patients were treated by decompressive surgery combined with transpedicular screw implantation and internal fixation. Patient baseline clinical characteristics were collected and compared between the two cohorts. Surgical outcomes analyzed included operation time; intraoperative blood loss; postoperative length of hospital stay; time to ambulation, regular diet, urinary catheter removal, and radiation therapy; perioperative complications; anxiety; depression; and satisfaction with treatment. Results: No significant differences in clinical characteristics were found between the non-ERAS and ERAS cohorts (all P > 0.050), indicating that the two cohorts were comparable. Regarding surgical outcomes, the ERAS cohort had significantly less intraoperative blood loss (P < 0.001); shorter length of postoperative hospital stay (P < 0.001); shorter time to ambulation (P < 0.001), regular diet (P < 0.001), urinary catheter removal (P < 0.001), radiation administration (P < 0.001), and systemic internal therapy (P < 0.001); lower perioperative complication rate (P = 0.024); less postoperative anxiety (P = 0.041); and higher score for satisfaction with treatment (P < 0.001); whereas operation time (P = 0.524) and postoperative depression (P = 0.415) were similar between the two cohorts. Compliance analysis demonstrated that ERAS interventions were successfully conducted in the vast majority of patients. Conclusions: The ERAS intervention is beneficial to patients with MESCC, according to data on intraoperative blood loss; length of hospital stay; time to ambulation, regular diet, urinary catheter removal, radiation exposure, and systemic internal therapy; perioperative complication; alleviation of anxiety; and improvement of satisfaction. However, clinical trials to investigate the effect of ERAS are needed in the future.